Prediction Model for Determination of Indications for Laser or Surgical Treatment for Aggressive Posterior Retinopathy of Prematurity at the Manifestation Stage - A. V. Tereshhenko; I. G. Trifanenkova; Yu. A. Sidorova; M. S. Tereshhenkova; E. V. Erohina; S. V. Isaev (Oftalʹmologiâ)
The purpose: to analyze anthropometric and diagnostic parameters in children with aggressive posterior ROP at the manifestation stage on its basis to build a predictive model, which allows to determine the indications for laser or surgical treatment.Patients and methods. The study included 111 children (190 eyes) with aggressive posterior ROP at the manifestation stage. 67 children (134 eyes) underwent transpupillary retinal laser photocoagulation (LPC) in the period from 2008 to 2013. In 46 children (82 eyes) the disease regression was archived (group 1), in 31 children (52 eyes) the progression continued (group 2), so at the second stage early lens-sparing vitrectomy was performed (2–4 weeks after LPC). In 34 children (56 eyes) primary lens-sparing vitrectomy was performed in the period from 2013 to 2017 (group 3). Anthropometric and diagnostic data for all patients were subjected to statistical analysis for building a predictive model.Results. The predictive model was based on logistic regression that determines the probability of separation of children with aggressive posterior ROP to the manifestation stage on treatment methods: transpupillary LPC or primary vitrectomy. The following parameters were selected: the diameter of the central arteries and tortuosity index (TI). All groups were joined into a single array to create the model, which allowed to differentiate the patients according to the treatment types based on the input data processing. It was obtained the equation of the logistic regression: Z = exp(55,2726 – 0,1584X – 35,3911Y) / (1 + exp(55,2726 – 0,1584X – 35,3911Y)), where Z has the value from 0 to 1.0; X value is the diameter of the central artery of the patient; Y — the value of the TI arteries of the patient. If Z < 0.5, then the patient has indications for surgical treatment, if Z > 0.5 — for laser treatment.Conclusion. The predictive model was obtained that with a probability of 96% allows to determine objectively the optimal treatment method for children with aggressive posterior ROP at the manifestation stage of the disease: transpupillary LPC or primary vitrectomy. This will increase the effectiveness of treatment of the severe and prognostically unfavourable forms of ROP. This model can be a “working” tool for ophthalmologists involved in the treatment of ROP, its introduction into the clinical practice is advisable.